Mise En Curvre Des Stratégies De Tutorat Par Les Pairs (Fille/ Garçon) Dans La Construction Des Connaissances Au Secondaire De L'enseignement Générale Au Cameroun Par (Global Journal of Human-Social Science, 2020)
In a context dominated by patriarchy, we tend to value the boy as a key social actor. The school, by reproducing socially accepted norms, gives priority to young boys. Quite often, he is appointed as class leader, as tutor for his peers. The objective of this research is to verify whether there is a significant link between peer (girl/boy) tutoring strategies and knowledge building. The study adopts a quantitative estimate through a knowledge test. The comparison of student t-test averages leads to the conclusion that any learner (girl/boy) at the head of a group contributes to the development of their peers' knowledge. Secondly, the construction of knowledge does not depend on how the groups were formed.
Keywords: tutoring; peers; knowledge building; secondary; general education